Organizational dedifferentiation: neural gradient axes and communication hierarchy in healthcare organizations - Moeki Nemoto (Frontiers in Communication, 2026)
Communication failures remain a leading cause of sentinel events in healthcare settings, yet the mechanisms by which organizational communication hierarchies form, function, and fail remain undertheorized. Prior work reconceptualized the Balanced Scorecard (BSC) as a constitutive communication mechanism through Communication Constitutes Organization (CCO) four flows theory; however, a principled account of why such hierarchies erode over time was lacking. This paper proposes that three functional gradient axes of the human neocortex—sensory-association (SA), modulation-representation (MR), and visual-somatosensory (VS)—offer a disciplined analogy for the communication hierarchy of healthcare organizations: the SA axis maps onto vertical strategic integration in BSC implementation; the MR axis parallels the tension between organizational self-structuring and activity coordination in CCO theory; and the VS axis corresponds, more loosely, to interprofessional communication differentiation and integration. Drawing on the neuroscientific finding that gradient differentiation follows an inverted-U trajectory and declines through dedifferentiation, the concept of organizational dedifferentiation is introduced: progressive erosion of communication hierarchy in mature healthcare institutions, manifesting as SA collapse, MR rigidification, and VS homogenization. Unlike existing lifecycle theories, this framework offers a candidate mechanism, a tentative collapse sequence, and three diagnostic indicators—SA coherence index, MR balance ratio, and VS integration score—proposed as measurable in principle before overt communication failure occurs. Active constitutive BSC use is proposed as a functional organizational analogue of cognitive reserve—by analogy rather than biological equivalence—that may help sustain communication hierarchy against dedifferentiation. This perspective opens a new interdisciplinary research agenda at the intersection of organizational communication theory and cognitive neuroscience.